Serapias occidentalis ("Orchidaceae"): appearance and distribution - Pessoa, Joaquim; Borges, Luísa; Venhuis, Caspar (Lazaroa, 2011)
Serapias occidentalis was known until recently only from Spanish Extremadura. The authors found the first population of S. occidentalis outside Extremadura in western Portugal. Like the Extremaduran populations, S. occidentalis in Portugal is quite variable morphologically as well as in flower colour. We assume that plants described as Serapias maria are representatives of S. occidentalis with relatively small flowers.